The extraterritorialisation of asylum and the advent of protection lite - Thomas Gammeltoft-Hansen (Danish Institute for International Studies (DIIS), 2007)
When does the refugee encounter the State? The straightforward and traditional answer to this question would be, when arriving at the border and surrendering herself to the authorities uttering the magical word, asylum. Reality, however, only seldom conforms to this picture. Today, the person seeking asylum in the EU is much more likely to encounter the State before reaching the EU border - at the visa consulate, through the EU Immigration Liaison Officers posted at the airports of key migration transit and origin countries, during passage over the Mediterranean where navy vessels are patrolling. Alternatively, the refugee may not meet EU in persona, but through delegation, either in the form of an airline company bound by EU regulations ro carry out migration control or as a third State having in EU cooperation to perform exit border control or provide alternative protection in the region. This paper explores the growing nexus of these external or extraterritorial policies in the developing EU asylum and immigration policv. From a legal perspective, these developments create a number of challenges for ensuring the rights of asylum seekers and refugees. Looking into three contentious areas (extraterritorial jurisdiction, extraterritorial protection and extraterritorial policy implementation) it is argued that the present drive to move migration control and refugee protection outside the EU is becoming a strategic feature of the common EU asylum and immigration policy, in which States are instrumentalising the territorial principles of the present refugee regime to relieve themselves of international legal obligations and institutionalise a new ethos of ''protection lite.
Keywords: 330; Migrationspolitik; Asylrecht; Einwanderungsrecht; Flüchtlinge; EU-Staaten